PENGARUH PERSEPSI WAJIB PAJAK ATAS PEMBERLAKUAN PERATURAN PEMERINTAH NOMOR 23 TAHUN 2018, PEMAHAMAN PERPAJAKAN, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK USAHA MIKRO, KECIL, DAN MENENGAH DI KOTA MEDAN - Syahputra, Heri Enjang; Purba, Rosanna; Sitompul, Andre Agasi Subandi (JURNAL MUTIARA AKUNTANSI, 2020)
Taxpayer Perceptions of the Enforcement of PP No. 23/2018, Understanding Taxation, and Tax Sanctions affect the Compliance of Taxpayers for Micro, Small and Medium Enterprises in Medan City. The population in this study is 1,016 Taxpayers for Micro, Small and Medium Enterprises who are registered at the Office of Cooperatives and Micro, Small and Medium Enterprises, Medan City. The sample in this study was 91 taxpayers for Micro, Small and Medium Enterprises in Medan City. The data collection method is a questionnaire that is distributed to respondents. The analysis prerequisite test includes normality test, linearity test, heteroscedasticity test, and multicollinearity test. Data analysis techniques used are partial significant test analysis (t-test), simultaneous significant test analysis (F-test), and the coefficient of determination (R -Square). The results of the partial and simultaneous analysis show that the Taxpayers' Perception of the Enforcement of Government Regulation No. 23/2018, Understanding of Taxation, and Tax Sanctions have a significant effect on Taxpayer Compliance for Micro, Small and Medium Enterprises in Medan City. The linear regression equation Y = 0.985 + 0.579X1 + 0.295X2 + 0.360X3 + e also shows a positive effect. Variations or changes in MSME Taxpayer Compliance can be explained by variations in the Taxpayer's Perception of the Enforcement of Government Regulation No. 23 of 2018, the understanding of taxation and tax sanctions is R2 = 24.8%, and has a strong enough relationship of R = 0.498.